2021
DOI: 10.48550/arxiv.2109.13293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quadratic Metric-Affine Gravity: Solving for the Affine-Connection

Damianos Iosifidis

Abstract: We consider the most general 11 parameter parity even quadratic Metric-Affine Theory whose action consists of the usual Einstein-Hilbert plus the 11 quadratic terms in torsion, non-metricity as well as their mixing. By following a certain procedure and using a simple trick we are able to find the unique solution of the affine connection in terms of an arbitrary hypermomentum. Given a fairly general non-degeneracy condition our result provides the exact form of the affine connection for all types of matter. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
1
5
0
1
Order By: Relevance
“…It is obvious then, by direct substitution of the latter form of the distortion into (62) that apart from the usual energy-momentum tensor quadratic and derivative terms of the hypermomentum serve also as sources producing gravitational fields. Our result above serves as a generalization of the earlier findings of [42] where now the additional six parity odd quadratic scalars have been added into the action along with the 11 parity even ones. Our study now covers the whole spectrum of quadratic MAG theories, that is we have found the exact form of the connection and consequently that of torsion and non-metricity for the most general 17 parameter quadratic MAG action.…”
Section: Post Riemannian Expansion Of the Metric Field Equationssupporting
confidence: 68%
See 3 more Smart Citations
“…It is obvious then, by direct substitution of the latter form of the distortion into (62) that apart from the usual energy-momentum tensor quadratic and derivative terms of the hypermomentum serve also as sources producing gravitational fields. Our result above serves as a generalization of the earlier findings of [42] where now the additional six parity odd quadratic scalars have been added into the action along with the 11 parity even ones. Our study now covers the whole spectrum of quadratic MAG theories, that is we have found the exact form of the connection and consequently that of torsion and non-metricity for the most general 17 parameter quadratic MAG action.…”
Section: Post Riemannian Expansion Of the Metric Field Equationssupporting
confidence: 68%
“…On the other hand, there is no parameter choice (except the trivial of vanishing coefficients) for which the parity odd terms cancel. Now, using a post-Riemannian expansion for every term in (42), after some lengthy calculations (see appendix for details) we finally arrive at…”
Section: Post Riemannian Expansion Of the Metric Field Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…(A.3)Finally, let us write the following post-Riemannian expansions (cf. also[54]):R µν = Rµν + − (−12 − 7n + 2n 2 + n 3 ) 4[(n − 1)(n + 2)] 2 Q λ Q λ + (−10 − 7n + n 3 ) 2[(n − 1)(n + 2)] 2 Q λ q λ + 2(n + 1) [(n − 1)(n + 2)] 2 q λ q λ 3n + 2 Q λ S λ + 2(n 2 − n − 4) n 3 − 3n + 2 q λ S λ − 4(n − 2) (n − 1) 2 S λ S λ − (n + 3) 2(n − 1)(n + 2) ∇λ Q λ + (n + 1) (n − 1)(n + 2) ∇λ q λ − 2 n − 1 ∇λ S λ g µν + (n 3 − 7n − 10) 4[(n − 1)(n + 2)] 2 Q µ Q ν + 4(n + 1) [(n − 1)(n + 2)] 2 Q (µ q ν) − (n 2 + n + 2) [(n − 1)(n + 2)] 2 q µ q ν + 2(n 2 − n − 4) n 3 − 3n + 2 Q (µ S ν) + 3n + 2 q (µ S ν) + 4(n − 2) (n − 1) 2 S µ S ν + (n + 1) 2(n − 1)(n + 2) ∇µ Q ν − (n 2 − 3) 2(n − 1)(n + 2) ∇ν Q µ − 2 (n − 1)(n + 2) ∇(µ q ν) − 2(n − 2) n − 1 ∇ν S µ , (A.4) R = R − (n 2 − 5) 4(n − 1)(n + 2)…”
unclassified